Federal Theatre - Marionette Theatre presents "RUR" Remo Bufano director. - Dux, Alexander, artist (New York : Federal Art Project, between 1936 and 1939, 1936)
Poster for Federal Theatre Project presentation of "RUR" at the Marionette Theatre, showing abstract image with text.